10.2k views
1 vote

{( √(3) )}^(x + y)  = 9 \\ {( √(2) )}^(x - y)  = 32

find the value of 2x + y.​

1 Answer

3 votes


\bf \purple{ \underline{Given :-}}


• \:  {( √(3) )}^(x + y)  = 9\:  \:  \: \: (i)


• \:  {( √(2) )}^(x - y)  = 32 \:  \:  \: \: (ii)


\\


\bf \purple{ \underline{To  \: Find :- }}


•   {\sf{The  \: value  \: of}} \:   \: 2x+ y.


\\


\huge\bf \purple{ \underline{Solution :- }}


\sf{From \:  equation \:  (i), }


{( √(3) )}^(x + y)  = 9


⇒ {( √(3) )}^(x + y)  =  ({ √(3) })^(4)


⇒ x + y = 4 \:  \:  \: \: (iii)


\\


\sf{From \:  the  \: equation \:  (ii)}


{( √(2) )}^(x - y)  = 32


⇒( { √(2) })^(x - y)  =(  { √(2) })^(10)


⇒x - y = 10 \:  \:  \: \: (iv)


\\


\sf{We \:  have \:  to  \: add \:  equation \:  (iii)  \: and \:  equation  \: (iv)}


x + y + x - y = 4 + 10


⇒2x = 14


⇒x = 7


\\


\sf{Subtracting \:  equation \:  (iii)  \: from  \: equation  \: (ii),  }


x  - y - x - y = 10 - 4


⇒ - 2y = 6


⇒y =  - 3


\\


\bf\therefore x = 7 \: \:  and  \: \: y =  - 3


\\


{ \sf{Th e \:  value \:  of }}= 2x +y


\:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \: \: \: \: \: \: =2 * 7  + ( - 3)


\:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \: \: \: \: \: \: =14 - 3


\:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \: \: \: \: \: =11


\bf \red{Hence,  \: the  \: value \:  of  \: 2x + y  \: is  \: 11. }

User Mgrouchy
by
5.6k points